Prescriptions are not Enough - Ferraro, Fabrizio; Pfeffer, Jeffrey; Sutton, Robert I. (Academy of Management Review, 2005)
According to Bazerman, economics has achieved its position of dominance simply because it provides prescriptions whereas other social sciences do not. We challenge his argument by showing that other social sciences do offer prescriptive advice but are nonetheless rarely influential. We argue that the mechanisms through which economics and other social sciences gain influence and affect practice should be investigated more carefully by management scholars seeking to understand how to have greater impact on both public policy and management practice.